Evaluation of interdepartmental calls generated in 8 tertiary care hospitals of Northern Pakistan - Arif, Anum; Hamza, Ali; Ahsin Manzoor Bhatti; Riaz, Bismah; Zia, Ammar; Ahmed , Yashfeen (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the quality of medical call writing in multiple tertiary care hospitals based on a variety of parameters. Method: The cross-sectional study was conducted in 8 tertiary care hospitals across Pakistan from May 27 to June 27, 2021, and comprised residents and consultants aged 25-60 years regardless of gender and specialty. Data was collected using questionnaires related to demographic and professional characteristics, quality of calls received, quality of calls sent, and opinion regarding improvements to the existing system. Data ws analysed using SPSS 22. Results: Of the105 participants, 65(62%) were residents and 40(38%) were consultants. General surgery team received referrals most frequently 26(24.7%). History of the patient along with relevant examination findings were mentioned in 4(3%) and 6(5%), respectively (p=0.6 vs p=0.5). The timeline was mentioned by 10(9.5%), (p=0.09), and it was inconsistent with the clinical relevancy in 13(12.3%) cases (p=0.5). The working diagnosis for which the patient was admitted in a particular service was mentioned in 35(33.3%) of the generated calls (p=0.01). Conclusion: The call referral system deserved more attention in order to improve communication among the physicians. Analysis of the quality of referral letters should be part of initial and continuing medical education. Key Words: Communication, Call system, Electronic medical record, Referral system.